Appraisal of prescription writing skills of preclinical undergraduate students in a medical institute of Nepal - Kumar, J; Shaik, MM; Kathi, MC; Chetty, MS; Deka, A (Journal of College of Medical Sciences-Nepal, 2012)
The aim of this study was to appraise the prescription writing skills of preclinical undergraduate students of College of Medical Sciences, Bharatpur. This prospective study was conducted over each of 150 of 1st year and 2nd year medical students in the months of May and June 2010 under the guidelines of World Health Organization (WHO). Prescriber’s identity, patient’s identity, the diagnosis, the symbol-Rx and prescriber’s signature were available on 90% and above of the prescriptions written by both year students. A large number of them also mentioned the prescriber’s address and the date of prescription. The information, instructions, warnings and patient’s address were the most deficient aspects among prescriber’s related components and the strength, the quantity to be dispensed and the direction for the use of drugs were the deficient aspects of drug related components. Comparatively more deficiencies were noted for drug related components. As an overall, the performance of 2nd year medical students was better than that of the 1st year. This study reveals that the prescription writing skills of preclinical medical students were sub-optimal and need emphasis for some elements during their clinical years and internship. However, there is a good scope of learning this skill also in the existing method of pharmacology teaching. Journal of College of Medical Sciences-Nepal,2011,Vol-6,No-4, 7-13 DOI: http://dx.doi.org/10.3126/jcmsn.v6i4.6719